Comparing Mid-Term Outcomes Between ACDF and Minimally Invasive Posterior Cervical Foraminotomy in the Treatment of Cervical Radiculopathy. Issue 4 (15th February 2022) - Emami, Arash; Coban, Daniel; Changoor, Stuart; Dunn, Conor; Sahai, Nikhil; Sinha, Kumar; Hwang, Ki Soo; Faloon, Michael
Abstract : ACDF has become one of the most commonly performed procedures by spinal surgeons and regarded as the gold-standard surgical treatment for cervical radiculopathy. MI-PCF is a safe and effective alternative to ACDF, demonstrating substantial benefit. MI-PCF demonstrated superior improvements in VAS scores, without increased complication or revision rates. Abstract : Study Design: Retrospective cohort study. Objective: To compare minimally invasive posterior cervical foraminotomy (MI-PCF) and anterior cervical discectomy and fusion (ACDF) in the treatment of unilateral cervical radiculopathy. Summary of Background Data: MI-PCF has been shown to be equally effective as ACDF in treating cervical radiculopathy due to foraminal stenosis and similar pathologies. Additionally, it has been hypothesized that preserving motion and avoiding fusion reduces risk for adjacent segment disease, but potentially increases risk for subsequent revision to an ACDF. With similar short-term outcomes and substantial advantages, MI-PCF may be an effective alternative to ACDF for addressing appropriate cervical pathology. Methods: A retrospective review was performed to identify patients between 2009 and 2013 who underwent ACDF or MI-PCF with a minimum follow-up of 7 years. Demographic data was recorded. Revision rates and average time to revision between cohorts were compared. Clinical outcomes were assessed at each follow-up visit with Neck Disability Index and Visual Analog Scale for neck and Visual Analog Scale for arm pain scores. All complications were reviewed. Standard binomial and categorical comparative analysis were performed. Results: A total of 251 consecutive patients were included (205 ACDF, 46 MI-PCF). Mean follow-ups for the ACDF and MI-PCF groups were 98.3 and 95.9 months, respectively. Complication rates were 2.9% and 2.2% for the ACDF and MI-PCF cohorts, respectively ( P  = 0.779). Revision rates were 7.8% for the ACDF cohort and 8.7% for the MI-PCF cohort ( P  = 0.840). Both cohorts experienced significant improvements in their clinical scores compared with their preoperative values. Final Visual Analog Scale for neck pain (ACDF: 2.6; MI-PCF: 1.6) and Visual Analog Scale for arm pain (ACDF: 1.1; MI-PCF: 0.4) scores differed significantly at final follow-up ( P  =  < 0.001; P  =  < 0.001). Conclusion: MI-PCF is a safe and effective alternative to ACDF in the treatment of cervical radiculopathy, demonstrating substantial benefit. After final follow-up, MI-PCF demonstrated superior improvements in Visual Analog Scale scores, without increased complication or revision rates. Level of Evidence: 3